KEPUTUSAN PEMBELIAN MELALUI KUALITAS MAKANAN, KUALITAS PELAYANAN, DAN LOKASI PADA NK CAFÉ MALANG - Teguh Widodo (Jurnal Manajemen dan Profesional, 2022)
The purpose of the study was to determine the effect of food quality, service quality, and location variables on consumer decisions at NK Café Malang. The data used is the result of distributing questionnaires to consumers. The sample selection technique is Accidental Sampling with a total of 50 consumers. Data processing uses multiple linear regression and is free from the classical assumption test. Consumer decisions are explained by 47.6% of the independent variables. The results show that the variables of food quality, service quality, and place have a significant effect on consumer purchasing decisions. Based on the results of the study, it shows that NK Café must maintain the values ​​of the three variables even if it needs to be increased.